Evolution of Shallow and Deep Structures Along the Maipo-Tunuyán Transect (33°40 S): From the Pacific Coast to the Andean Foreland - Jara-Munoz, P (Geological Society of London, 2015)
We propose an integrated kinematic model with mechanical constrains of the Maipo-Tunuyán transect (33°40 S) across the Andes. The model describes the relation between horizontal shortening, uplift, crustal thickening and activity of the magmatic arc, while accounting for the main deep processes that have shaped the Andes since Early Miocene time. We construct a conceptual model of the mechanical interplay between deep and shallow deformational processes, which considers a locked subduction interface cyclically released during megathrust earthquakes. During the coupling phase, long-term deformation is confined to the thermally and mechanically weakened Andean strip, where plastic deformation is achieved by movement along a main décollement located at the base of the upper brittle crust. The model proposes a passive surface uplift in the Coastal Range as the master décollement decreases its slip eastwards, transferring shortening to a broad area above a theoretical point S where the master detachment touches the Moho horizon. When the crustal root achieves its actual thickness of 50 km between 12 and 10 Ma, it resists further thickening and gravity-driven forces and thrusting shifts eastwards into the lowlands achieving a total Miocene-Holocene shortening of 71 km. © 2015 The Geological Society of London.